Integrated management of Spodoptera frugiperda 6 years post detection in Africa: a review - Tepa-Yotto, G.; Chinwada, P.; Rwomushana, I.; Goergen, Georg E.; Subramanian, S. (Elsevier, 2022)
The introduction of fall armyworm (FAW) Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae) on the African continent has led to paradigm shifts in pest control in maize systems, occasioned by year-round populations. The discovery of resident parasitoid species adapting to the new pest significantly informed decision-making toward avoiding highly hazardous synthetic insecticides to control the pest. A number of biopesticides have shown promise against the fall armyworm, providing a new arsenal for the sustainable management of this invasive pest. However, a few knowledge gaps remain for a fully integrated and sustainable FAW-management approach, particularly on host-resistance potential.